THE URGENCY OF APPLICATION OF THE ROCCIPI METHOD IN FORMING VILLAGE REGULATIONS REGARDING THE PROTECTION AND MANAGEMENT OF PEAT AND MANGROVE ECOSYSTEMS IN KUBU RAYA REGANCY - Hamdani Hamdani; Muhammad Syafei; Haryadi Haryadi; Oktaviani Yenny; Chatrine Sabendi Putri (PRANATA HUKUM, 2023)
Issues regarding Peat and Mangrove Ecosystem Management Arrangements are often discussed and become a problem in a region. There are many questions that arise, especially how to provide protection and management of peat and mangrove ecosystems and what are the wishes of the community, especially the village community, in formulating regulations regarding peat and mangroves. In fact, special methods are needed in regulating and formulating peat and mangrove regulations. For this reason, the ROCCIPI method is an alternative to making village regulations governing the Protection and Management of Peat and Mangrove Ecosystems. This study aims to discuss the urgency of implementing the ROCCIPI Method in Forming Village Regulations Concerning the Protection and Handling of Peat and Mangrove Ecosystems in Kubu Raya Regency. The research method uses descriptive qualitative. Data collection was carried out by observation and in-depth interviews. The withdrawal of informants was done on purpose. Data analysis used Miles and Huberman's interactive model which began with data collection, data reduction, data presentation and drawing conclusions. The results of the study show that the ROCCIPI method is very relevant to be used/applied in the preparation of Village Regulations concerning the Protection and Management of Peat and Mangrove Ecosystems in Kubu Raya Regency.